2012
DOI: 10.2967/jnumed.111.101899
|View full text |Cite
|
Sign up to set email alerts
|

Fast Spiral SPECT with Stationary γ-Cameras and Focusing Pinholes

Abstract: Small-animal SPECT systems with stationary detectors and focusing multiple pinholes can achieve excellent resolutionsensitivity trade-offs. These systems are able to perform fast total-body scans by shifting the animal bed through the collimator using an automated xyz stage. However, so far, a large number of highly overlapping central fields of view have been used, at the cost of overhead time needed for animal repositioning and long image reconstruction times due to high numbers of projection views. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Previously, we showed that mouse organs and entire bodies can be imaged with half-minute time frames using high-resolution focused multipinhole SPECT (16,17). Because VECTor has a better sensitivity than these SPECT systems (both for SPECT and PET tracers), we expect that similar time resolutions will be feasible, allowing, for example, tracer kinetic modeling in simultaneous SPECT/PET.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we showed that mouse organs and entire bodies can be imaged with half-minute time frames using high-resolution focused multipinhole SPECT (16,17). Because VECTor has a better sensitivity than these SPECT systems (both for SPECT and PET tracers), we expect that similar time resolutions will be feasible, allowing, for example, tracer kinetic modeling in simultaneous SPECT/PET.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high-end commercial smallanimal PET attains image resolutions of approximately 1 mm (10)(11)(12)(13)(14)(15) and cannot distinguish between simultaneously injected tracers, because positron emission from different tracers results in g-photon pairs with equal energy (511 keV). Recently, it was also shown that fast dynamic (total body) imaging is possible with small-animal SPECT based on stationary detectors (16,17). This ability makes SPECT, besides PET, an important tool in, for example, kinetic modeling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer's software was used for acquisition (version 3.4f) and reconstruction (b version, VECTor 1 ). List-mode acquisitions used the scanning focus method (8) with helical bed motions (9) to move the animal through the hourglass-shaped FOV, which encompasses the entire bore (diameter, 4.8 cm) and has an average length of 3.6 cm. For a mouse brain, 19 bed positions were used.…”
Section: Scanner Descriptionsmentioning
confidence: 99%
“…All clustered pinholes together observe a field of view that has the shape of an hourglass with a diameter of 44 mm and an average longitudinal length of 33 mm (10). Total-body images are obtained by moving the animal through the scanner along a spiral trajectory (13). Data are collected in list-mode.…”
Section: Small-animal Imaging Systemmentioning
confidence: 99%